Peran Aktif Pemuda Karang Taruna Pujut dalam Pengembangan Desa Wisata Strategi Peningkatan Keterampilan dan Wawasan - Putri Rizkiyah; Royanow, Achlan Fahlevi; Fahmi, Saiful; Muhtasom, Ali; Satiadji, Amirosa Ria (LPPPM STAI Darul Hikmah Bangkalan, 2024)
The development of tourist villages is a crucial strategy for boosting local economies while preserving culture and the environment. An example is the Kuta Mandalika Tourism Village in Central Lombok Regency, which has joined the Jadesta platform. To optimize the potential of this tourist village, Karang Taruna Pujut needs skill enhancement, particularly in tour package development, barista training, and entrepreneurship. This study aims to enhance the capacities of Karang Taruna Pujut members through a Technical Assistance program conducted by the Center for Research and Community Service (P3M) at Politeknik Pariwisata Lombok. The implementation method involves three stages: training, field visits, and action plan presentations. Over four days, participants were divided into three groups and received training and field visits in Bali. The results indicate an improvement in participants' skills and knowledge, with innovative action plans designed for the development of the tourist village. Participant feedback was positive, reflecting the program's success in broadening their tourism expertise and the active role of Keywords: active role, karang taruna, tourism village, community service